The Fundamentality of Human Genetics Identity as a Transgenerational Right - Rodrigueiro, Daniela A. (2016)
From fiction to reality, post-modern society unfolded the unrestrained search for a human ideal that approaches perfection. Social expectations and scientific truths, unattached from value judgment, for centuries have allowed leaps previously unimaginable by the life sciences. However, it was not long before a light was seen as a warning signal from the international community. It is a human right of intertemporal dimension. The need for a dialogue among the sciences of knowledge is imperative. Therefore, once we’ve indentified Hans Jonas’ Imperative of Responsibility and Ulrich Beck’s Risk Society, the precautionary principle presents itself as a safe north.